The Perception of Jantho City 1 High School Students on Physics Learning Using Youtube Channel - Yuni Syahraini; Elisa Elisa; A Halim (Universitas Syiah Kuala, 2019)
This study aims to determine the perceptions of Jantho City 1 Senior High School students towards the use of the youtube channel as a medium for learning physics. This type of research is descriptive research. The approach used in this study is a qualitative approach, where the sample in this study were all 24 students of senior high school 1 Kota Jantho High School students. The data collection techniques used were questionnaires or questionnaires to obtain data on the perceptions of Jantho City 1 Senior High School students on the use of the youtube channel in physics learning. Processing data using the percentage formula (%). The results of the overall student show that 54% of students perceive strongly agree, 46% of students perceive agree, 0% of students have moderate perceptions, 0% of students perceive disagree, and 0% of students at SMA 1 Kota Jantho perceive strongly disagree with the use of media channels youtube in physics learning. Where the average student has a very good perception of learning physics using the youtube channel